The effects of rope jump training on sprint, agility, jump and balance tests in young basketball players - Boccolini, G.; Costa, N.; Alberti, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Rope jumping has been a major training tool for many sports like boxing and tennis. In recent years, it has also been a favourite training tool for basketball players in addition to many other training options. Studies in the literature have demonstrated that the rope jump training is a valid training method for volleyball players [1], and that weighted rope jumping is a viable alternative to high impact plyometric exercises [2]. The aim of this study is to evaluate the effects of rope jump training on sprint, agility, jump and balance tests in young basketball players METHODS: The study was conducted on 28 amateur basketball players of two different team. The players were randomly divided into two groups: Rope Group (RG; n=14; 14.0±0.0 yr; height 169.6±11.1; weight 59.1±11.3) and Control Group (CG; n=14; 14.0±0.0 yr; height 164.1±8.3; weight 52.0±10.0). In this way, and (19.1±4.8 yr; height 176.8±5.8; weight 69.6±7.8). RG received a technical training program and in addition a rope jump training twenty minutes per session, three times a week, for four weeks. Rope training consisted always in jumps forwards. The control group followed only a technical training program for the same duration. Before and after four weeks, sprint test on 10m (SpT), lane agility drill test (LADT), stiffness test (StT), counter movement jumps test (CMJ) and balance test (BaT) have been performed. CMJ and BaT have been performed on one and two legs. All subjects performed 3 trials for each tests. The data were analyzed using paired T-test using SPSS software v. 17 (SPSS Inc, Chicago, IL). The significant level was set up to p<.05. RESULTS: Following rope jump training, the RG obtained significant improvement in SpT (p<.001), LADT (p<.001), StT (p<.001), CMJ with right leg (p<.05) and BaT (p<.05) for 3.76%, 3.07%, 6.29%, 7.24% and 13.37% respectively. Regarding the CG, there were no significant increases in any of the variables analyzed. DISCUSSION: These findings indicate that rope jump training is a valid method to improve the sprint capacity on 10m, the agility test, the stiffness and balance ability with two legs. We suggest to use rope jump training during warm-up and also strength and coordinative trainings